The ancient world goes digital: case studies on archaeology, texts, online publishing, digital archiving, and preservation - Bigot Juloux, Vanessa; Di Ludovico, Alessandro; Matskevich, Sveta (Digital biblical studies, 2023)
This volume presents fourteen case studies in digital humanities and digital archaeology applied to the research of the written sources and the material culture of the Ancient Near East and in the Biblical studies.